Synthetic data as a strategy to resolve data privacy and confidentiality concerns in the sport sciences: Practical examples and an R Shiny application - Naughton, M.; Weaving, D.; Scott, T.; Compton, H. (International Journal of Sports Physiology and Performance, 2023)
Purpose: There has been a proliferation in technologies in the sport performance environment that collect increasingly larger quantities of athlete data. These data have the potential to be personal, sensitive, and revealing and raise privacy and confidentiality concerns. A solution may be the use of synthetic data, which mimic the properties of the original data. The aim of this study was to provide examples of synthetic data generation to demonstrate its practical use and to deploy a freely available web-based R Shiny application to generate synthetic data.